Role of thromboxane in impaired renal vasodilatation response to acetylcholine in hypercholesterolemic rats. - Bank, N (1992)
Short-term cholesterol feeding has been shown to cause impaired vasodilatation in response to acetylcholine. The present study of renal hemodynamics was carried out to examine the role of thromboxane/PGH2 in mediating this abnormal response. In normal rats (ND), infusion of acetylcholine into the suprarenal aorta caused marked increases in renal blood flow, GFR, single nephron glomerular filtration rate, single nephron afferent plasma flow, and ultrafiltration coefficient, accompanied by a fall in preglomerular resistance. In cholesterol fed rats (CSD), the response to acetylcholine was markedly blunted. Infusion of L-arginine, the precursor to nitric oxide (NO), caused comparable renal vasodilatation in ND and CSD rats, implying that the ability to synthesize NO from its precursor was not severely impaired in the CSD animals. The observations do not exclude, however, the possibility of impaired synthesis of NO from endogenous precursor. In additional experiments, we infused a TxA2/PGH2 receptor antagonist in CSD rats and then administered acetylcholine. Renal vasodilatation occurred to a degree indistinguishable from that in ND rats given acetylcholine alone. When ND rats were infused with the same combination of the TxA2/PGH2 receptor antagonist and acetylcholine, renal vasodilatation was also significantly greater than with acetylcholine alone. This suggests that acetylcholine initiates release of vasoconstrictor prostanoids as well as NO from vascular endothelium. This was observed in ND as well as in CSD animals. Because LDL increases the supply of arachidonic acid for prostaglandin synthesis, we postulate that greater amounts of PGH2/TxA2 are synthesized via calcium activation of phospholipase A2 when acetylcholine is administered to CSD animals. This may account in large measure for the blunted vasodilatation to acetylcholine.